Physical properties of glue / Razwan Abdullah - Abdullah, Razwan (1994)
The works cover in this final year project is to determine the Modulus of Elasticity, £ and Poisson's ratio, U of glue due to tensile load. The experimental laboratory tests consist of determining the Modulus of Elasticity with different duration time, day. The results' data from the experimental analysis i.e Modulus of Elasticity will be used in the finite element analysis with various values of Poisson's ratio and will results the different value of stresses and displacements. The plotted graph for Poisson's ratio vs. displacement will give the Poisson's ratio value for that Modulus of elasticity. The analysis of wood joint covers the butt joint analysis. Isoparametric solid 2-D element i.e plane 42 is used in the analysis.Linear finite element model and the aspect ratio is limited to 1:10 were in order to reduce the errors. It was found that the value for Modulus of Elasticity increase with the increase of Poisson's ratio.